Shahbandar and Waliyah: Islamic Female Leadership in Gresik (11th-15th Centuries) - Wirawan, Abdul Karim; Rosyidah, Ulfa (Islah: Journal of Islamic Literature and History, 2025)
This study aims to analyze two models of female leadership in Islam in Gresik during the formative period (11th -15th centuries) by comparing Siti Fatimah binti Maimun (d. 1082 CE) and Nyai Ageng Pinatih (active 1458-1477 CE). Employing microhistory and feminist historiography methodologies, the research reveals two distinct forms of authority: spiritual genealogical leadership (Waliyah) and structural-maternal leadership (Shahbandar). Siti Fatimah established her authority through Islamic genealogy and religious scholarship, reflected in her monumental tomb complex. Meanwhile, Nyai Ageng Pinatih utilized administrative competence and political networks as the shahbandar (port master) of Gresik port. The findings demonstrate the flexibility of the Nusantara Islamic social system in accommodating female leadership through diverse legitimation mechanisms, challenging the religious-secular authority dichotomy. Moreover, the research also reveals the disparity in collective memory between the two figures, reflecting gender bias in Indonesian Islamic historiography. In conclusion, this study contributes to understanding the complexity of female leadership traditions in Indonesian Islam and its relevance to contemporary gender debates.